An investigation of the approaches for integrating learning materials and digital games: a prior ability perspective - Huang, Ben-Gao; Yang, Jie Chi; Chen, Sherry Y. (Universal access in the information society, 2021)
Learning materials are integrated into digital games in digital game-based learning (DGBL). There are two types of contexts to present such integration, i.e., tightly coupling context (TCC) and loosely coupling context (LCC). These two types of contexts have different strengths and weaknesses. On the other hand, prior abilities have great effects on DGBL. Accordingly, this study aims to examine the effects of the TCC and LCC on DGBL from a prior ability aspect. Regarding the TCC, low-ability students and high-ability students obtained similar gain scores. On the other hand, the post-test scores of high-ability students were significantly better than their pre-test scores in the TCC while such a significant difference was not found for low-ability students. Regarding the LCC, high-ability students acquired significantly higher gain scores than low-ability students. Furthermore, students’ post-test scores were significantly higher than their pre-test scores in the LCC, regardless of low-ability students or high-ability students. Implications for system design are also discussed.